ELUCIDATION OF POTATO TUBER RESPONSE TO FUSARIUM SOLANI VAR COERULEUM INFECTION TRANSCRIPTOME ANALYSIS - W. Wen-Zhong; 3√; Z. Tong2√; G. Rui; C. Ling-Ling; F. Peng; Z. Zong-Bao; Y. Shuai; W. Qi; G. Mei; M. Fan-Xiang; H. Lin-Shuang; et al. (Journal of Animal and Plant Sciences, 2020)
Dry rot in potatoes, caused by Fusarium spp. is a global critical post harvest fungal disease. To explore the response of Solanum tuberosum cv. Kexin No.13 to Fusarium solani var. coeruleum in potato tuber, we measured gene expression changes after 72 h pathogen inoculation by Illumina sequencing. The transcriptome analysis was used to identify candidate resistance genes and to dissect the early molecular processes. Of these, 4,262 differentially expressed genes (DEGs) were identified. The data were further confirmed by real-time PCR. The data indicated that F. solani var. coeruleum infection triggered DEGs were associated jasmonic acid (JA) and ethylene (ET) signaling pathways. Moreover, six kinds of transcription factors, three kinds of proteases and pathogenesis-related proteins (PRs) were also up-regulated in potatoes after pathogen inoculation. Overall, our findings give a broader view of the dynamic changes of the potato transcriptome triggered by F. solani var. coeruleum and highlights that the resistance response of potato is mainly signaled by JA and ET pathways, transcription factors, proteases, and PRs to enhance the host defence ability in potato tubers. All these could provide a genetic and molecular level foundation for the study on resistance to potato dry rot.
Keywords: Fusarium solani var. coeruleum; molecular pathological response; Solanum tuberosum; transcriptome